A Novel Electroosmotic Micromixer with Asymmetric Lateral Structures and DC Electrode Arrays - Limin Chen (Micromachines, 2017)
We present a novel electroosmotic micromixer that consists of arrays of direct current (DC) asymmetric electrode and asymmetric lateral structures. By embedding asymmetric electrode arrays on the top and bottom walls of a rectangular microchannel appropriately, the flow perturbations and vortexes can be induced when a DC electric field is imposed. An efficient lateral structure is then sequentially combined with the rectangular microchannel, which enhances the mixing effect significantly. The effects of operational parameters such as the Reynolds number, the applied potential, and the Peclet number on the mixing performance are analyzed in detail by numerical simulations. The results indicate that an enhanced mixing performance can be achieved with low applied potential. The novel method proposed in this paper provides a simple solution for mixing in the field of micro-total-analysis systems.